Iron Overload-induced Ferroptosis as a Target for Protection against Obliterative Bronchiolitis after Orthotopic Tracheal Transplantation in Mice - You, Yun; Wang, Guoliang; Cui, Qi; Sun, Xiangfu; Wan, Li; Sun, Quanchao (Current Molecular Medicine, 2025)
IntroductionThe major complication of Obliterative Bronchiolitis (OB) is characterized by epithelial cell loss, fibrosis, and luminal occlusion of the terminal small airways, which limits the long-term survival of the recipient after lung transplantation. However, the underlying mechanisms are still not fully clarified. This research aims to investigate whether iron overload-induced ferroptosis is involved in OB development and provide a new target for OB prevention.Materials and MethodsAllograft orthotopic tracheal transplantation in mice was applied in our study. Ferrostatin-1 and deferoxamine were administrated to inhibit ferroptosis and get rid of ferric iron, while iron dextran was used to induce an iron overload condition in the recipient. The histological examination, luminal occlusion rate, collagen deposition, iron level, ferroptosis marker (GPX4, PTGS2), and mitochondrial morphological changes of the graft were evaluated in mice.ResultsOur research indicated that ferroptosis and iron overload contribute to OB development, while ferroptosis inhibition and iron chelator could reverse the changes. Iron overload exacerbated OB development after orthotopic tracheal transplantation via promoting ferroptosis.ConclusionOverall, this research demonstrated that iron overload-induced ferroptosis is involved in OB, which may be a potential therapeutic target for OB after lung transplantation.
Keywords: ferroptosis